The Effect of Using Word Wall Website on Students’ Vocabulary Achievement - Susilowati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Vocabulary is one of the important aspects of English language skills. However, in reality, there are still many students who have difficulty in remembering and using vocabulary appropriately in context. This has an impact on students' low ability to understand reading texts and compose sentences in speaking English. This happens to high school students. Academically, high school students have a demand to develop their English, so they have to expand and deepen their vocabulary. Therefore, teachers have an important role in guiding students in mastering vocabulary. Along with the times, teachers can use various technologies to facilitate English teaching, especially at the junior high school level. However, unfortunately not many teachers are able to maximize technology for English teaching. In fact, more interesting, interactive, and appropriate learning media is needed, such as digital media. This study aims to determine whether the use of Word Wall Website digital media can have a significant effect on vocabulary achievement of students in grade VII. Word Wall is a website-based media that allows teachers to create various types of fun and visual vocabulary exercises, such as matching words with pictures. Hopefully, this media can increase students' interest in learning and help them remember vocabulary more easily. The method used in this research is quantitative method with quasiexperimental design. The research was conducted on two groups of seventh grade students, namely the experimental group and the control group. The experimental group was treated by using Word Wall media in learning vocabulary of procedure text material, while the control group learned using conventional methods without the help of digital media, such as using dictionary books or asking the teacher. Data were collected through a post-test given after the treatment to measure vocabulary mastery. The data analysis technique used was the Mann-Whitney U test to see the difference in learning outcomes between the two groups. The mann whitney test was conducted because it did not fulfill the prerequisite test, namely the normality test. The results showed that there was a significant difference between the posttest scores of the experimental and control groups. The experimental group using Word Wall media obtained higher scores, which shows that this media is effective in helping students understand and remember vocabulary. In addition, students in the experimental group also seemed more enthusiastic and active during the learning process. Based on these results, it can be concluded that the use of Word Wall Website as a digital learning media can improve the vocabulary achievement of seventh grade students. This media not only helps students in understanding the meaning of words visually but also makes the learning process more fun. Therefore, it is recommended that English teachers consider using Word Wall or similar digital media in the vocabulary learning process to create a more interactive and effective classroom atmosphere.
Reupload File Repositori 5 Februari 2026_Rudy K/Lia
Keywords: Word Wall Website